Democratization and autocratization in comparative perspective concepts, currents, causes, consequences, and challenges - Møller, Jørgen 1979-; Skaaning, Svend-Erik 1978- (Routledge, Taylor & Francis Group, 2024)
"This book provides balanced, critical, and comprehensive coverage of the theories and realities of autocratization and democratization. It sketches developments in the conceptions of democracy, discusses how to distinguish between different forms of political rule, and maps the development of democracy and autocracy across space and time. The book reviews the major debates and findings about domestic and international causes and consequences of democratization and autocratization. It synthesizes theoretical models and empirical relationships based on an explicit comparative perspective, which focuses on similarities and differences across countries and historical periods. Key features: - offers a coherent framework, which students and scholars can use to grasp the literature on democratization and autocratization as a whole - includes tables and figures as well as plentiful, illustrative in-text features, including chapter summaries, text boxes, concluding bullets points, and discussion questions - fully updated to account for the recent developments within the relevant literatures as well as global and regional patterns of democratization and autocratization - a section on democracy and autocracy today, highlighting important political challenges for democracy, such as populism and polarization, and providing an overview of the level of democratic crisis in developed democracies Democratization and Autocratization in Comparative Perspective will be essential reading for students and scholars of political science, democracy and democratization, comparative politics, political theory, and international relations"--
Literaturverzeichnis: Seite 295-330, Register
Keywords: Democracy; Authoritarianism